2003
DOI: 10.1002/elps.200305573
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in capillary electrokinetic chromatography with replaceable charged pseudostationary phases or additives

Abstract: Although electrochromatography in packed beds or monolithic columns has gained enormous interest, techniques based on charged pseudostationary phases like micelles are of high practical importance in electrically driven separation science. However, nonmicellar alternatives, e.g., using charged soluble polymers or smaller additives are still attractive, as they allow high concentrations of organic solvents, and their application is not limited by the critical micellar concentration. This review discusses the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Potential for peptide separations can be expected also from other CEKC modes with replaceable charged pseudostationary phases and additives [143,144] and from microemulsion EKC (ME-EKC) [145].…”
Section: Electrokinetic Chromatographymentioning
confidence: 99%
“…Potential for peptide separations can be expected also from other CEKC modes with replaceable charged pseudostationary phases and additives [143,144] and from microemulsion EKC (ME-EKC) [145].…”
Section: Electrokinetic Chromatographymentioning
confidence: 99%
“…Dendrimers can also be used as a pseudostationary phase for micellar electrokinetic chromatography [8,11]. Stathakis et al [12] demonstrated the usability of various generations, G0 (cationic), 0.5, 1.5, 2.5 and 3.5 (anionic), for the separation of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Two reviews by this author in this journal concentrated on studies of the performance and selectivity of polymeric PSPs from their introduction in 1992 until 1997 [5,6]. Since that time, several other reviews have detailed the development and selectivity of polymeric PSPs [10][11][12][13][14]and the development and characterization of chiral polymeric PSPs. [9] The current review will consider those developments and studies with polymeric and dendrimeric PSPs since the previous reviews by this author in this journal in 1997.…”
Section: Introductionmentioning
confidence: 97%